Polysaccharide from Cumaru (Amburana cearensis) exudate and its potential for biotechnological applications - José Regilmar Teixeira da Silva; Iranildo Costa Araújo; Eziel Cardoso da Silva; Moisés das Virgens Santana; Geanderson Emilio de Almeida; Emanuel Airton de Oliveira Farias; Laís Ramos Monteiro de Lima; Regina Célia Monteiro de Paula; Durcilene Alves da Silva; Alyne Rodrigues Araújo; Carla Eiras (Polímeros, 2024)
Abstract Amburana cearensis tree is used in various applications, from artisanal to pharmaceutical use. However, the gum extracted from its exudate has not yet been investigated. This study aimed to the physicochemical and structural characterization of Amburana cearensis Gum (AcG) by elemental, rheological, and thermal analyses, X-ray diffraction (XRD), high-Performance Liquid Chromatography (HPLC), Gel Permeation Chromatography (GPC), Infrared Spectroscopy (FTIR), UV-Vis spectroscopy and nuclear magnetic resonance (NMR). Additionally, a hemolytic assay was performed to evaluate the biocompatibility of AcG using human erythrocytes. The results showed that AcG consists of β-D-Galactopyranose monomers linked by glycosidic bonds (1→3). At the same time, the side chains exhibit β-Galactopyranose (1→6) and α-L-Arabinofuranoside (1→3,6) monomers as non-reducing terminals, whose biocompatibility was excellent in the model used. AcG was described for the first time as a biopolymer that could have broad applications in the pharmaceutical and cosmetic industries, justifying the interest in further studies about AcG applications.